Dry season water allocation in the Mae-taeng Irrigation Project, Thailand - Mandot, Ramesh Kumar; Loof, Rainer; Paudyal, Guna N.; Gupta, Ashim Das; Canadian International Development Agency, Government of Canada (Bangkok : Asian Institute of Technology, 1989)
Management of irrigation water under the irregular and limited availability is still a complicated issue for the irrigation planners. Selection of a suitable cropping pattern and accordingly to schedule the irrigation in these circumstances is a challenge for them. The issue aggravates when a greater participation in cultivation is desired under mixed cropping pattern scenario. The present study deals with such a problematic Irrigation Project in northern Thailand, where, in the absence of a controlled water resource, the available streamflow proves too less to meet the potential crop water needs in the dry season. To allocate lands to the different prevailing crops and accordingly to schedule the available irrigation water, a model was developed. The · model is based on three main factors i.e. weekly irrigation water demand of the crops, expected available water and sensitive crop growth stages. On the basis of these factors, an irrigation strategy was developed with the idea of extensive irrigation under limited streamflow. According to that strategy, instead of allocating areas to different crops, the least water available in the most critical week is distributed between the crops. The distribution criteria has been left at the discretion of the irrigation planner. Crops are supplied deficit irrigation in that week and the savings in water are used for extending the cultivated area. Irrigation water shortage in the other weeks is distributed between the crops in proportion to their extended area. The effect of water stresses on the yield is assessed by the weekly yield response factors (Ky). The maximum adverse effect of the deficit irrigation occurring during any of the weeks of the growth stage is taken as the effect on the final yield. Depending upon the cropped area distribution, the model sets the irrigation schedules for the secondary canals. The model was applied for different overall project efficiencies and probable availability of streamflow. The strategy used under the study proved a success for the project. This is reflected by the achievements of the set goals of maximum farmers participation, greater production and gross production values on a global basis.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1989
Keywords: Mae Taeng Irrigation Project; Irrigation -- Management